Gylan Bin Salama Al thakafi `s Life and Poetry - Habib, wahran (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research deals with one of the most maven poets who is Gylan Bin Salama Al thakafi. He lived between two period which are the pre- Islamic era and the Islamic one. His poetry may got lost with what was lost of poetry , or what was told verbally. We preferred to gather his scattered/separated poems in novels , literature and history books ,with little mentioning to his news which were told by narrators , written in various valuable sources which we worked hard following them in order to enliven a treasure of our Arabic heritage treasures and providing the Arabic library with one of the great figures of our Arab poetry. We have divided the work in this research into two sections: one deals with the poet's life concerning his name, parentage ,his life, news, his espousing Islam, his tribe, his cultural formation and his death . As for the second section, it deals with his poetry which we have arranged its poems alphabetically according to the dash of the last letter of each line of the poem. We have organized the lines accurate and explained the difficult vocabulary as we mentioned the difference in the narration in the lines whether there were more than one narration in order to make Gylan 's poetry available to every reader.